The Constitution of the Republic of Iraq of 2005: between the mechanisms and the necessity of amendment - Ali Essa Al-Yaqoobi (Journal of Legal Sciences, 2024)
The Constitution of the Republic of Iraq of 2005 is considered an important transformation in the constitutional life in Iraq and represented the beginning of an important phase in its political history. As a result of the change in the political system in 2003, this constitution was written in a very sensitive and complex circumstance. However, on the other hand, it represented an important opportunity to reformulate the political system and the form of the state and draw the boundaries of public rights and freedoms on new foundations. Although constitutional experiments in the world often stipulate mechanisms for amending them according to need and the development of circumstances and are classified accordingly as flexible and rigid constitutions, the Iraqi constitutional experience, as a result of many factors, stipulated two mechanisms for amending the provisions of the 2005 Constitution. The Iraqi Constitution, although its articles were designed to be a relatively rigid constitution, it stipulated a mechanism for a comprehensive, exceptional, and one-time review of its provisions. In addition to and as an exception to the regular amendment contained in Article 126. From another angle, the debate over whether or not the amendment is necessary represents another important axis for any serious discussion about the future of constitutional reform in Iraq between those who see the necessity of the amendment to overcome the negatives of the establishment stage and those who believe that the existence of this newborn has not yet been completed so that will be tried for not enacting most of the laws complementary to its implementation.